P PENERAPAN SISTEM PENDUKUNG KEPUTUSAN PADA PENILAIAN KINERJA KARYAWAN MENGGUNAKAN METODE FUZZY-ANALYTIC HIERARCHY PROCESS (F-AHP) (STUDI KASUS : PT. GAJAH MITRA PARAGON) - Arujisaputra, Erwin Teguh; Yohanes, Patar (Jurnal Teknologi Informasi, 2025)
Employee performance is important for the company, employee performance needs to be assessed to achieve one of the management goals. Employee performance appraisal at PT Gajah Mitra Paragon requires development so that the results of the assessment are quickly accepted by management as decision makers, when the results are received early, the determination of employees to get rewards when the results of the assessment are good, and receive an evaluation or transfer because the results of the assessment are not good. The application of a Decision Support System in evaluating employee performance uses the Fuzzy-Analytic Hierarchy Process (F-AHP) logic which is an analytical method used in handling qualitative and quantitative criteria in Multi Criteria Decision Making (MCDM). The results of the analysis state that an application is needed for evaluating employee performance by determining criteria, weights and inputting computerized assessments with faster results or outputs. After the implementation, it can be concluded that this employee performance appraisal application greatly facilitates the company in getting the results of the performance appraisal for employees, the company can know for sure the best employees as well as employees who must receive an evaluation because the results of the assessment are not satisfactory. Even with the Fuzzy-Analytical Hierarchy Process (F-AHP) method, it can still be developed or replaced with other methods with the same goal. Keyword : Information System, Employee Performance, DSS, Fuzzy AHP